When we had wings - Lawhon, Ariel; McMorris, Kristina; Meissner, Susan, 1961- (Harper Muse, 2022)
"Based on real history and alternating between three perspectives, When We Had Wings tells an amazingly moving story of heroic service, perseverance in the darkest of days, and the hope of the human spirit"--